Effects of Bupivacaine Versus Bupivacaine Plus Dexamethasone-Soaked Nasal Packing After Endoscopic Nasal Surgery. Issue 4 (June 2019) - Yayik, Ahmet Murat; Yildirim, Hasan; Ahiskalioglu, Ali; Sakat, Muhammed Sedat; Ergüney, Özlem Dilara; Ahiskalioglu, Elif Oral; Sulak, Muhammet Mustafa; Celik, Erkan Cem
Abstract : Background: The aim of this randomized prospective study was to investigate the postoperative analgesic effectiveness of bupivacaine versus bupivacaine plus dexamethasone-soaked nasal packing in patients scheduled for endoscopic nasal surgery. Methods: Sixty American Society of Anesthesiologists groups I and II patients aged 18 to 65 years and scheduled for endoscopic nasal surgery were assigned into 2 groups. Group B received 8 mL 0.5% bupivacaine and 2 mL saline, and group BD received 8 mL 0.5% bupivacaine and 8 mg (2 mL) dexamethasone-soaked nasal packing. In the postoperative period, 1000 mg paracetamol was administered and repeated every 6 hours. Postoperative pain scores, additional analgesia requirements and nausea-vomiting were recorded. Results: Postoperative pain scores were significantly lower in group BD than in group B at 1, 2, 4, 8, and 12 hours, and during tampon removal ( P < 0.05), but there was no difference between the groups' 24-hour visual analog scale scores ( P = 0.115). Postoperative additional analgesia use was statistically significantly higher in group B than in group BD (25/30 versus 13/30 respectively, P = 0.001). Postoperative nausea and vomiting was statistically higher in group B than in group BD (11/30 versus 4/30 respectively, P = 0.037). Conclusion: The addition of dexamethasone to bupivacaine via soaked nasal packing in endoscopic nasal surgery reduced postoperative pain scores, additional analgesia requirements, and PONV. The authors recommended a combination of bupivacaine plus dexamethasone-soaked nasal packing after endoscopic nasal surgery.